2015
DOI: 10.3102/0002831215599251
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Sensemaking of Data and Implications for Equity

Abstract: This article examines an understudied aspect of teachers’ sensemaking of student learning data: the way in which teachers explain the causes of the outcomes observed in data. Drawing on sensemaking and attribution theory and data collected in six middle schools, we find that while teachers most often attributed outcomes to their own instruction, they also frequently focused on supposedly stable student characteristics. By citing these characteristics as explanations for the results analyzed, teachers may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 53 publications
(96 reference statements)
10
169
1
Order By: Relevance
“…The purpose of this study is to improve understanding of the conditions of data use that support organizational learning about inequitable policies and practices and how to go about changing them. The study contributes to the literature on data use and organizational change (e.g., Bensimon & Hanson, 2012;Bertrand & Marsh, 2015;Coburn & Turner, 2012;Dowd & Tong, 2007;Horn, Kane, & Wilson, 2015;Kezar, 2011Kezar, , 2014Marsh, 2012) by illustrating how local institutional reformers can effectively use and adapt data and data use protocols made available to them through state and national initiatives that include practitioner inquiry as an element of the change process.…”
Section: Introductionmentioning
confidence: 98%
“…The purpose of this study is to improve understanding of the conditions of data use that support organizational learning about inequitable policies and practices and how to go about changing them. The study contributes to the literature on data use and organizational change (e.g., Bensimon & Hanson, 2012;Bertrand & Marsh, 2015;Coburn & Turner, 2012;Dowd & Tong, 2007;Horn, Kane, & Wilson, 2015;Kezar, 2011Kezar, , 2014Marsh, 2012) by illustrating how local institutional reformers can effectively use and adapt data and data use protocols made available to them through state and national initiatives that include practitioner inquiry as an element of the change process.…”
Section: Introductionmentioning
confidence: 98%
“…Another important dimension of mathematics-related beliefs are beliefs that express stereotypes about the ability to learn mathematics (Braeken and Blömeke 2016) including group-specific stereotypes towards students with special needs or second-language learners (Bertrand and Marsh 2015). When holding such beliefs, teachers might show different expectations towards children viewed as 'less able' resulting in a self-fulfilling prophecy (Rosenthal and Jacobson 1968).…”
Section: Preschool Teacher Education In Germanymentioning
confidence: 99%
“…However, when data are examined in a more superficial manner, teachers may not have an opportunity to dig deeply into these kinds of questions (Hoover and Abrams, 2013) and assumptions can go unexamined. Even more troubling, Bertrand and Marsh's (2015) study found that when educators used student characteristics as an explanation for results, they deflected attention away from their own practice and reinforced a culture of low expectations.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Although few studies to date (for an exception see Bertrand and Marsh, 2015) focus specifically on the equity-data use intersection, a number of prior studies have uncovered findings that reveal that potentially significant equity implications. For example, Lachat and Smith (2005) found that using data can help address false assumptions about the root causes of student achievement patterns.…”
Section: Guest Editorialmentioning
confidence: 99%
See 1 more Smart Citation